The Impact of Total Quality Management on Company Performance on the X Online Transportation Service Platform in Bali - Putu Diri Adnyana; Ni Ketut Purnawati (Indonesian Journal of Business Analytics, 2026)
Company performance is the primary benchmark for assessing how well an organization can survive and compete. In the gig economy, a company’s success depends heavily on effective resource management to maintain service quality for users. Therefore, this study was conducted to examine how implementing total quality management affects the company’s performance. Using quantitative methods, data were collected from 140 active driver-partners via convenience sampling and analyzed with multiple linear regression in SPSS. The results of the study showed that simultaneously, the TQM dimension had a positive and significant influence on the company’s performance. Partly, the focus on customers and the efficiency of the operational system proved to be the dominant factors driving the company’s performance in Bali. However, the education and training dimensions were found not to affect the company’s performance. These findings suggest that system reliability and service quality in the field determine performance stability more than formal training programs do.